THE EFFECTIVENESS OF LEARNING DEVICES OF EARTH AND SPACE PHYSICS ORIENTED INQUIRY MODELS TO IMPROVE CRITICAL THINKING SKILL OF STUDENTS - Dina Syaflita; Muhammad Nor (Jurnal Geliga Sains: Jurnal Pendidikan Fisika, 2018)
Physics of earth and space is one of the subject that learn about natural phenomena. Leraning activity that learn about nature require students to be able to think logically and critically about a phenomena. Therefore, learning models and learning tools are needed that support lecture activity that allow students to construct knowledge through experiments and gather various information. The fact found that the lectures of earth and space physics that are used today are still conventional. This does not support the improvement of student’s critical thinking skill. One solution that can be done is to develop lecture devices consisting of worksheets oriented to inquiry models and earth teaching aids which are implemented in lectures. The aim of this research is to obtain the effectivity value of the devices of earth and space physics lecture to improve the critical thinking skill of students. Data collection instrument is pretest and posttest before and after use the product. Data analysis technique use t-test correlates with product moment. The result of this research is the worksheet of earth and space physics oriented inquiry model is effective improve of student’s critical thinking skill with the value of the product moment is 60%.